2022 25th International Conference on Information Fusion (FUSION) 2022
DOI: 10.23919/fusion49751.2022.9841376
|View full text |Cite
|
Sign up to set email alerts
|

Detection of outliers in classification by using quantified uncertainty in neural networks

Abstract: Neural Networks (NNs) can solve very hard classification and estimation tasks but are less well suited to solve complex sensor fusion challenges, such as end-to-end control of autonomous vehicles. Nevertheless, NN can still be a powerful tool for particular sub-problems in sensor fusion. This would require a reliable and quantifiable measure of the stochastic uncertainty in the predictions that can be compared to classical sensor measurements. However, current NN's output some figure of merit, that is only a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Furthermore, the second derivative of the likelihood function approximates the inverse of the Fisher information matrix. In [29], it was shown that for a classification problem, the Fisher information is given by…”
Section: A Laplacian Approximation and The Delta Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the second derivative of the likelihood function approximates the inverse of the Fisher information matrix. In [29], it was shown that for a classification problem, the Fisher information is given by…”
Section: A Laplacian Approximation and The Delta Methodsmentioning
confidence: 99%
“…The high computational complexity is particularly true for NN classifiers, which have a huge dimension of the parameter space. In [29], a remedy to this is presented, which reduces the dimension in the sampling to an M -dimensional space. In this paper, it is done using the so-called delta method [36,38].…”
Section: B Fusion Using Parametric Modelsmentioning
confidence: 99%
See 3 more Smart Citations